A development study and randomised feasibility trial of a tailored intervention to improve activity and reduce falls in older adults with mild cognitive impairment and mild dementia - Harwood, Rowan H.; van der Wardt, Veronika; Goldberg, Sarah E.; Keamey, Fiona; Logan, Pip; Hood-Moore, Victoria; Booth, Victoria; Hancox, Jennie E.; Masud, Tahir; Hoare, Zoe; Brand, Andrew; Tudor Edwards, Rhiannon; et al. (Biomed Central, 2018)
Background: People with dementia progressively lose abilities and are prone to falling. Exercise- and activity-based interventions hold the prospect of increasing abilities, reducing falls, and slowing decline in cognition. Current falls prevention approaches are poorly suited to people with dementia, however, and are of uncertain effectiveness. We used multiple sources, and a co-production approach, to develop a new intervention, which we will evaluate in a feasibility randomised controlled trial (RCT), with embedded adherence, process and economic analyses.